Shale oil carbon dioxide flooding surfactant and preparation method thereof

By combining fluorine-containing copolymers, sodium dodecylbenzenesulfonate and nanoparticles surfactants, the oil recovery problem in the high temperature and high salt environment of the shale oil reservoir is solved, and the recovery rate and oil flooding efficiency are improved.

CN120399667AActive Publication Date: 2025-08-01DESHI ENERGY TECH GRP CO LTD

Patent Information

Application Number
CN202510875089.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-08-01
Estimated Expiration
2045-06-27

AI Technical Summary

Technical Problem

Existing surfactants are not effective in high-temperature, high-pressure, and high-salt shale oil reservoirs, and it is difficult to meet the demand for carbon dioxide flooding of shale oil.

Method used

By combining the fluorine-containing copolymer with sodium dodecylbenzenesulfonate, silicon-oxygen-containing polyoxyethylene ether surfactant and nanoparticles, a surfactant with high salt resistance and temperature resistance is formed, which jointly improves surfactant, reduces interfacial tension, changes the wettability of the rock surface, and enhances the stability of the system.

Benefits of technology

It achieves a high recovery rate in high temperature and high salt environment, reduces interface tension, and enhances oil flooding efficiency, and is suitable for the carbon dioxide oil flooding process of shale oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120399667A_ABST
    Figure CN120399667A_ABST
Patent Text Reader

Abstract

The invention discloses a shale oil carbon dioxide flooding surfactant and a preparation method thereof, and belongs to the technical field of surfactants. The rock oil carbon dioxide flooding surfactant is prepared from the following components in parts by weight: 100 parts of water, 40 to 60 parts of fluorine-containing copolymer, 15 to 25 parts of sodium dodecyl benzene sulfonate, 10 to 20 parts of polyoxyethylene ether surfactant containing siloxy and 5 to 10 parts of nanoparticles. The fluorine-containing copolymer, the sodium dodecyl benzene sulfonate, the siloxy-containing polyoxyethylene ether surfactant and the nanoparticles are compounded, so that on one hand, the surfactant has relatively high salt tolerance and temperature tolerance so as to adapt to the environment of a shale oil reservoir; on the other hand, the surface activity is synergistically improved, the interfacial tension is reduced, the rock surface wettability is changed, and the system stability is enhanced, so that higher recovery efficiency is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a surfactant for carbon dioxide flooding of shale oil and a preparation method thereof, belonging to the technical field of surfactants. Background Art

[0002] Shale reservoirs usually have poor physical properties, extremely fine pores and throats, and the forms of shale oil existing in the formation are relatively complex. Usually, in high-temperature, high-pressure, and high-salt environments, conventional water injection, chemical agent injection, thermal oil recovery, microbial oil recovery and other measures often cannot achieve good development effects.

[0003] The CO2 huff and puff oil recovery technology is a widely used development technology for improving the recovery rate of low-permeability reservoirs and tight reservoirs. Gas injection development can effectively improve the physical properties of the reservoir, reduce the viscosity of the crude oil in the reservoir, and expand the volume of the crude oil. Compared with water flooding, gas injection development has become an important measure to effectively improve the recovery degree of shale oil reservoirs.

[0004] To improve the mining effect, various additives are often used to assist CO2 to further improve the recovery rate. Among them, surfactants are one of the commonly used additives. On the one hand, a large amount of foam will be generated in-situ after the surfactant contacts with CO2, which can selectively block high-permeability channeling channels, improve the reservoir heterogeneity and expand the swept volume; on the other hand, the surfactant can also reduce the interfacial tension, emulsify and disperse the crude oil and reduce the viscosity of heavy oil during the oil displacement process. For example, the surfactants disclosed in Patent CN105257264A include silicone ether surfactants and polyether surfactants; the selected silicone ether surfactants and polyether surfactants can reduce the minimum miscibility pressure between carbon dioxide and the original oil, thereby improving the original oil recovery rate. However, the above surfactants are only applicable to conventional oil reservoirs. For the special high-temperature, high-pressure, and high-salt environments of shale oil reservoirs, the functions of the above surfactants will be significantly reduced, and it is difficult to meet the mining requirements of shale oil. Therefore, matching surfactants are needed to meet the needs of carbon dioxide flooding of shale oil. Summary of the Invention

[0005] In order to solve the above problems, a surfactant for carbon dioxide flooding of shale oil and a preparation method thereof are provided. The surfactant for carbon dioxide flooding of shale oil is prepared by compounding a fluorinated copolymer with sodium dodecylbenzenesulfonate, a polyoxyethylene ether surfactant containing a siloxy group, and nanoparticles, so that the surfactant has high salt tolerance and high temperature resistance on the one hand to adapt to the environment of shale oil reservoirs; on the other hand, it synergistically improves surface activity, reduces interfacial tension, changes the wettability of the rock surface, enhances the stability of the system, and expands the swept volume of oil displacement, thereby achieving a high recovery rate.

[0006] According to one aspect of the present application, a surfactant for carbon dioxide flooding of shale oil is provided. By weight, it includes 100 parts of water, 40 - 60 parts of fluorinated copolymer, 15 - 25 parts of sodium dodecylbenzenesulfonate, 10 - 20 parts of polyoxyethylene ether surfactant containing siloxy groups, and 5 - 10 parts of nanoparticles; The nanoparticles include nano - silica and nano - alumina. The nano - silica includes modified nano - silica and unmodified nano - silica, and the modified nano - silica is obtained by modification with a silane coupling agent; The preparation method of the fluorinated copolymer includes the following steps: S01 Add diethylaminoethyl methacrylate, N - isopropylacrylamide, and dodecafluoroheptyl methacrylate into a reaction vessel in sequence, add deionized water, stir evenly and heat up to 60 - 80 °C; S02 Add an initiator into the reaction vessel, stir and react for 5 - 7 h under a nitrogen atmosphere, cool and reflux to room temperature to obtain a crude product; S03 The crude product is purified by dialysis and freeze - dried to obtain the fluorinated copolymer.

[0007] Specifically, by compounding the fluorinated copolymer with sodium dodecylbenzenesulfonate, polyoxyethylene ether surfactant containing siloxy groups, and nanoparticles, the surfactant has high salt tolerance and temperature resistance on the one hand to adapt to the environment of shale oil reservoirs; on the other hand, it synergistically improves surface activity, reduces interfacial tension, changes the wettability of the rock surface, and enhances the stability of the system, thereby achieving a high recovery rate.

[0008] Specifically, the fluorinated polymer provided in the present application is formed by free - radical polymerization of diethylaminoethyl methacrylate, N - isopropylacrylamide, and dodecafluoroheptyl methacrylate. The polymer chain contains an amino - ester structure with certain reactivity and adjustable properties brought by diethylaminoethyl methacrylate, an amide structure contributed by N - isopropylacrylamide, and a fluorocarbon chain structure introduced by dodecafluoroheptyl methacrylate that can enhance temperature resistance and change surface properties, making it have high temperature resistance and having obvious advantages in applications such as carbon dioxide flooding of shale oil.

[0009] Optionally, the molar ratio of diethylaminoethyl methacrylate to N - isopropylacrylamide is (3 - 5):1; the molar ratio of diethylaminoethyl methacrylate to dodecafluoroheptyl methacrylate is (1 - 3):1; the initiator is ammonium persulfate, and the mass of the initiator is 1 - 1.5% of the sum of the masses of the monomers.

[0010] Specifically, the present application makes specific limitations on the molar ratio of each monomer and the addition amount of the initiator to obtain a qualified fluorinated polymer.

[0011] Optionally, the mass ratio of the nano-silica to the nano-alumina is (2 - 5):1.

[0012] Specifically, in this application, nanoparticles are compounded with each component. On the one hand, the nanoparticles can adsorb on the surface of rock pores, change the surface properties of the rock, make it more hydrophilic, thereby reducing the adsorption amount of crude oil on the rock surface, which is beneficial to the displacement of crude oil; it can also block high-permeability channels and enhance the stability of the entire surfactant system at the same time; the nanoparticles and the surfactant act synergistically, and can further reduce the oil-water interfacial tension.

[0013] Specifically, in this application, nano-silica and nano-alumina are compounded. On the one hand, both of them have high chemical stability and thermal stability, and can better integrate into the surfactant system, enhance the stability of the system, and prevent components such as surfactants from prematurely precipitating, aggregating, etc.; on the other hand, they can change the pore structure and rock surface properties through adsorption, filling, etc., and improve the recovery rate of crude oil.

[0014] Optionally, the modified nano-silica is prepared by modifying silica with an amino-silane coupling agent.

[0015] Specifically, in this application, the nano-silica is modified with an amino-silane coupling agent. On the one hand, its dispersibility can be improved to avoid aggregation; on the other hand, the interaction with each component can be enhanced. After the nano-silica particles are amino-modified, the amino groups on their surface can interact with the acidic groups in the fluorinated copolymer and the sulfonic acid groups of sodium dodecylbenzenesulfonate, etc., better stabilizing the system structure and at the same time enhancing the synergistic effect in reducing the interfacial tension and other aspects.

[0016] The preparation method of the modified nano-silica is as follows: Disperse the nano-silica in absolute ethanol to obtain a suspension, add 3-aminopropyltriethoxysilane, stir and disperse evenly, and heat up to 60 - 80 °C, react for 3 - 6 h to obtain the modified nano-silica.

[0017] Specifically, the mass ratio of the nano-silica to the 3-aminopropyltriethoxysilane is (3 - 6):1.

[0018] Specifically, the particle size of the nano-silica is 20 - 50 nm, and the particle size of the nano-alumina is 50 - 100 nm.

[0019] Optionally, the preparation method of the silicon-oxy-containing polyoxyethylene ether surfactant includes the following steps: S1 Add γ-glycidoxypropyltrimethoxysilane and methoxypolyethylene glycol into a reaction vessel, add a catalyst, stir, and react at 70-90 °C for 3-5 h under a nitrogen atmosphere; S2 Add methanol to the reaction system, and react at 70-90 °C for 2-3 h under a nitrogen atmosphere to obtain a crude product; S3 Obtain a polyoxyethylene ether surfactant containing a siloxy group through vacuum distillation, dialysis, and concentration.

[0020] Specifically, first, through a silane coupling reaction, the siloxy group of γ-glycidoxypropyltrimethoxysilane (GPTMS) reacts with the hydroxyl group of methoxypolyethylene glycol (MPEG) to form an intermediate with a siloxy group and a polyoxyethylene ether segment while retaining the epoxy group; then, an epoxy ring-opening reaction is carried out, and methanol is added to open the epoxy group, further increasing the hydrophilicity and molecular chain flexibility of the product, and generating a crude product of a polyoxyethylene ether surfactant containing a siloxy group; finally, through post-treatment purification, low-boiling impurities are removed by vacuum distillation first, and then dialysis is carried out with a dialysis bag to further remove unreacted small-molecule raw materials and catalyst and other impurities, and finally a relatively pure polyoxyethylene ether surfactant containing a siloxy group is obtained.

[0021] Optionally, the molar ratio of γ-glycidoxypropyltrimethoxysilane to methoxypolyethylene glycol is 1:(1-1.3); the mass of the catalyst is 0.5-1% of the total mass of γ-glycidoxypropyltrimethoxysilane and methoxypolyethylene glycol; the molar ratio of methanol to methoxypolyethylene glycol is (1-2):1.

[0022] Optionally, the catalyst includes tetrabutylammonium hydroxide.

[0023] Specifically, tetrabutylammonium hydroxide can effectively catalyze the reaction between the siloxy group and the hydroxyl group under mild reaction conditions, accelerate the reaction rate and will not introduce too many impurities to affect the product performance.

[0024] According to one aspect of the present application, there is also provided a preparation method of the above surfactant for shale oil carbon dioxide flooding, including the following steps: (1) Add the fluorinated copolymer into water and stir evenly; (2) Add sodium dodecylbenzenesulfonate and a polyoxyethylene ether surfactant containing a siloxy group in sequence and stir evenly; (3) Ultrasonically disperse the nanoparticles in water to form a dispersion, add it to the mixed solution in step (2), stir, and then circulate and homogenize 2-3 times through a high-pressure homogenizer; (4) Adjust the pH value, cool to room temperature and filter to obtain the surfactant for shale oil carbon dioxide flooding.

[0025] Optionally, the temperature of water in step (1) is 40~50°C.

[0026] Optionally, the pressure of cyclic homogenization in step (3) is 1000~2000 PSI; the pH value in step (4) is 6~8.

[0027] Specifically, the homogenization treatment in step (3) can effectively disperse and mix various components therein more evenly, avoiding uneven phenomena such as agglomeration and stratification. Furthermore, the prepared surfactant product has good and stable properties, enabling it to play a better role in the subsequent application of carbon dioxide flooding for shale oil.

[0028] The beneficial effects of this application include but are not limited to: 1. For the surfactant for carbon dioxide flooding of shale oil according to this application, by compounding a fluorinated copolymer with sodium dodecylbenzenesulfonate, a polyoxyethylene ether surfactant containing a siloxy group, and nanoparticles, the surfactant has high salt tolerance and temperature resistance on the one hand to adapt to the environment of shale oil reservoirs; on the other hand, it synergistically improves surface activity, reduces interfacial tension, enhances system stability, and expands the swept volume of oil displacement, thereby achieving a high recovery rate.

[0029] 2. For the surfactant for carbon dioxide flooding of shale oil according to this application, the fluorinated polymer provided in this application contains an amino ester structure with certain reactivity and adjustable properties brought by diethylaminoethyl methacrylate, an amide structure contributed by N-isopropylacrylamide, and a fluorocarbon chain structure introduced by dodecafluoroheptyl methacrylate that can enhance temperature resistance and change surface properties in the polymer chain. Therefore, the fluorinated polymer is not only sensitive to carbon dioxide but also has the advantages of reducing surface tension, improving compatibility with carbon dioxide, and enhancing temperature resistance; the fluorinated polymer and sodium dodecylbenzenesulfonate act synergistically to improve the oil displacement efficiency.

[0030] 3. For the surfactant for carbon dioxide flooding of shale oil according to this application, due to the unique siloxy structure and polyoxyethylene ether chain segment of the polyoxyethylene ether surfactant containing a siloxy group, it has good compatibility with carbon dioxide and performs well in reducing interfacial tension and improving wettability. The nanoparticles and the surfactant act synergistically. On the one hand, they can reduce the adhesion force between the oil film and the rock, facilitate the detachment of oil droplets, and improve the oil displacement efficiency; on the other hand, they are beneficial to reducing the oil-water interfacial tension and maintaining the stability of the system.

[0031] 4. For the preparation method of the surfactant for carbon dioxide flooding of shale oil according to this application, the preparation method is simple and convenient for large-scale popularization and application. Description of the Drawings

[0032] The accompanying drawings described herein are used to provide a further understanding of the present application, and constitute a part of the present application. The schematic embodiments and descriptions thereof are used to explain the present application, and do not constitute an improper limitation of the present application. In the drawings: Figure 1 It is the 1H NMR spectrum of the fluorine-containing copolymer related to Example 1 of the present application.

[0033] Figure 2 It is the 1H NMR spectrum of the polyoxyethylene ether surfactant containing siloxy related to Example 1 of the present application. Detailed implementation manners

[0034] The present application will be described in detail below in conjunction with examples, but the present application is not limited to these examples.

[0035] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application are all purchased through commercial channels.

[0036] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art. The preparation method of the modified nano-silica involved in the following examples and comparative examples is as follows: Disperse nano-silica in absolute ethanol to obtain a suspension, add 3-aminopropyltriethoxysilane, stir and disperse evenly, and heat to 70 °C and react for 5 h to obtain modified nano-silica. The mass ratio of nano-silica to 3-aminopropyltriethoxysilane is 5:1, and the particle size of nano-silica is 30 nm; the particle size of nano-aluminum oxide involved in the following examples and comparative examples is 60 nm.

[0037] Example 1 A preparation method of a surfactant for carbon dioxide flooding of shale oil, comprising the following steps: (1) Weigh each raw material by weight, add 40 parts of the fluorine-containing copolymer to 100 parts of water, the temperature of the water is 40 °C, and stir evenly; (2) Add 15 parts of sodium dodecylbenzenesulfonate and 10 parts of the polyoxyethylene ether surfactant containing siloxy in sequence, and stir evenly; (3) Ultrasonically disperse 5 parts of nanoparticles in water to form a dispersion liquid, and add it to the mixed solution in step (2). The nanoparticles include modified nano-silica and nano-aluminum oxide, and the mass ratio of modified nano-silica to nano-aluminum oxide is 2:1; after stirring, circulate and homogenize 2 times by a high-pressure homogenizer, and the pressure of the circulation homogenization is 1000 PSI; (4) Adjust the pH value to 6, cool to room temperature and filter to obtain a surfactant for carbon dioxide flooding of shale oil with a mass fraction of 30%.

[0038] The preparation method of the fluorine-containing copolymer includes the following steps: S01 Add diethylaminoethyl methacrylate, N-isopropylacrylamide, and dodecafluoroheptyl methacrylate into a reaction vessel in sequence. Add deionized water, stir evenly, and heat up to 60 °C. The molar ratio of diethylaminoethyl methacrylate to dodecafluoroheptyl methacrylate is 1:1, and the molar ratio of diethylaminoethyl methacrylate to N-isopropylacrylamide is 3:1. S02 Add ammonium persulfate as an initiator into the reaction vessel. The mass of the initiator is 1% of the total mass of the monomers. Stir and react for 5 h under a nitrogen atmosphere, then cool and reflux to room temperature to obtain a crude product. S03 Purify the crude product by dialysis and freeze-dry it to obtain a fluorinated copolymer.

[0039] The preparation method of the polyoxyethylene ether surfactant containing siloxy groups includes the following steps: S1 Add γ-glycidoxypropyltrimethoxysilane and methoxypolyethylene glycol into a reaction vessel. The molar ratio of γ-glycidoxypropyltrimethoxysilane to methoxypolyethylene glycol is 1:1. Add tetrabutylammonium hydroxide as a catalyst. The mass of the catalyst is 0.5% of the total mass of γ-glycidoxypropyltrimethoxysilane and methoxypolyethylene glycol. Stir and react at 70 °C for 3 h under a nitrogen atmosphere. S2 Add methanol into the reaction system. The molar ratio of methanol to methoxypolyethylene glycol is 1:1. React at 70 °C for 2 h under a nitrogen atmosphere to obtain a crude product. S3 Obtain the polyoxyethylene ether surfactant containing siloxy groups through vacuum distillation, dialysis, and concentration.

[0040] Reference Figure 1 , 2 It can be seen that the fluorinated copolymer and the polyoxyethylene ether surfactant containing siloxy groups of this application have been successfully synthesized.

[0041] Example 2 A preparation method of a surfactant for carbon dioxide flooding of shale oil includes the following steps: (1) Weigh each raw material by weight. Add 60 parts of the fluorinated copolymer into 100 parts of water. The temperature of the water is 50 °C, and stir evenly. (2) Add 25 parts of sodium dodecylbenzenesulfonate and 20 parts of the polyoxyethylene ether surfactant containing siloxy groups in sequence, and stir evenly. (3) Ultrasonically disperse 10 parts of nanoparticles in water to form a dispersion liquid, and add it to the mixed solution in step (2). The nanoparticles include modified nano-silica and nano-aluminum oxide. The mass ratio of modified nano-silica to nano-aluminum oxide is 5:1. After stirring, circulate and homogenize 3 times with a high-pressure homogenizer. The pressure of the circulation homogenization is 2000 PSI. (4) The pH value was adjusted to 8, cooled to room temperature, and filtered to obtain a shale oil carbon dioxide flooding surfactant with a mass fraction of 30%.

[0042] The preparation method of the fluorine-containing copolymer comprises the following steps: S01: Diethylaminoethyl methacrylate, N-isopropylacrylamide, and dodecafluoroheptyl methacrylate are sequentially added into a reaction vessel, deionized water is added, the mixture is stirred evenly, and the temperature is raised to 80°C; wherein the molar ratio of diethylaminoethyl methacrylate to dodecafluoroheptyl methacrylate is 3:1; and the molar ratio of diethylaminoethyl methacrylate to N-isopropylacrylamide is 5:1; S02 Add initiator ammonium persulfate into the reaction vessel, the mass of the initiator is 1.5% of the mass of the monomers, The reaction was stirred under nitrogen atmosphere for 7 h, and then cooled to reflux to room temperature to obtain a crude product; The crude product S03 was purified by dialysis and freeze-dried to obtain a fluorinated copolymer.

[0043] The preparation method of the polyoxyethylene ether surfactant containing silicone group comprises the following steps: S1: adding γ-glycidyloxypropyltrimethoxysilane and polyethylene glycol monomethyl ether to a reaction vessel in a molar ratio of γ-glycidyloxypropyltrimethoxysilane to polyethylene glycol monomethyl ether of 1:1.3; adding a catalyst, tetrabutylammonium hydroxide, the mass of the catalyst being 1% of the total mass of γ-glycidyloxypropyltrimethoxysilane and polyethylene glycol monomethyl ether, stirring, and reacting at 90°C under a nitrogen atmosphere for 5 hours; S2: adding methanol to the reaction system at a molar ratio of methanol to polyethylene glycol monomethyl ether of 2:1, and reacting at 90°C for 3 h under a nitrogen atmosphere to obtain a crude product; S3 is subjected to reduced pressure distillation, dialysis and concentration to obtain a polyoxyethylene ether surfactant containing a silicone group.

[0044] Example 3 A method for preparing a shale oil carbon dioxide flooding surfactant comprises the following steps: (1) Weigh each raw material by weight, add 50 parts of fluorinated copolymer to 100 parts of water at a temperature of 45°C, and stir evenly; (2) Add 20 parts of sodium dodecylbenzenesulfonate and 15 parts of polyoxyethylene ether surfactant containing silicone group in sequence and stir evenly; (3) Ultrasonic dispersion of 7 parts of nanoparticles in water to form a dispersion, and adding the mixed solution in step (2), wherein the nanoparticles include modified nano-silica and nano-alumina, and the mass ratio of modified nano-silica to nano-alumina is 3:1; after stirring, the mixture is circulated and homogenized three times in a high-pressure homogenizer at a pressure of 1500 PSI; (4) Adjust the pH value to 7, cool to room temperature and filter to obtain a shale oil carbon dioxide flooding surfactant with a mass fraction of 30%.

[0045] The preparation method of the fluorine-containing copolymer comprises the following steps: S01: Diethylaminoethyl methacrylate, N-isopropylacrylamide, and dodecafluoroheptyl methacrylate are sequentially added into a reaction vessel, deionized water is added, the mixture is stirred evenly, and the temperature is raised to 70°C; wherein the molar ratio of diethylaminoethyl methacrylate to dodecafluoroheptyl methacrylate is 2:1; and the molar ratio of diethylaminoethyl methacrylate to N-isopropylacrylamide is 4:1; S02 is added into the reaction vessel as initiator ammonium persulfate, the mass of the initiator is 1.2% of the mass of the monomers, The reaction was stirred under nitrogen atmosphere for 6 h, and then cooled to reflux to room temperature to obtain a crude product; The crude product S03 was purified by dialysis and freeze-dried to obtain a fluorinated copolymer.

[0046] The preparation method of the polyoxyethylene ether surfactant containing silicone group comprises the following steps: S1: adding γ-glycidyloxypropyltrimethoxysilane and polyethylene glycol monomethyl ether to a reaction vessel in a molar ratio of γ-glycidyloxypropyltrimethoxysilane to polyethylene glycol monomethyl ether of 1:1.1; adding a catalyst, tetrabutylammonium hydroxide, in a mass of 0.7% of the total mass of γ-glycidyloxypropyltrimethoxysilane and polyethylene glycol monomethyl ether, stirring, and reacting at 80°C under a nitrogen atmosphere for 4 hours; S2: adding methanol to the reaction system at a molar ratio of methanol to polyethylene glycol monomethyl ether of 1.5:1, and reacting at 80°C for 2.5 hours under a nitrogen atmosphere to obtain a crude product; S3 is subjected to reduced pressure distillation, dialysis and concentration to obtain a polyoxyethylene ether surfactant containing a silicone group.

[0047] Example 4 The difference between Example 4 and Example 3 is that unmodified nano-silica is used to replace modified nano-silica in the nanoparticles, and the rest are the same.

[0048] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that the fluorine-containing copolymer is not included, and the rest are the same.

[0049] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that sodium dodecylbenzenesulfonate is not included, and the rest are the same.

[0050] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that nanoparticles are not included, and the rest are the same.

[0051] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that it includes 55 parts of fluorinated copolymer and does not include polyoxyethylene ether surfactants containing siloxy groups, and the rest are the same.

[0052] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that during the preparation process of the fluorinated copolymer, it does not include the monomer dodecafluoroheptyl methacrylate, and the rest are the same.

[0053] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that the number of parts of nanoparticles remains unchanged, and it only includes nano-aluminum oxide, and the rest are the same.

[0054] Test Example 1 Temperature and Salt Resistance Experiment Weigh 0.1 g of the surfactant for shale oil carbon dioxide flooding prepared in the examples and comparative examples and dissolve it in 100 mL of aqueous solutions with different salinities. Let it stand for 72 h at different temperatures and observe the state of the solution. The test results are shown in Table 1.

[0055] Table 1 Test Results of Temperature and Salt Resistance Performance

[0056] It can be seen from Table 1 that the surfactants for shale oil carbon dioxide flooding in Examples 1 to 3 can withstand high temperatures exceeding 135 °C and brines with a salinity greater than 25×10 4 mg / L. Compared with Examples 1 to 3, the high-temperature and salt resistance performance of Example 4, Comparative Example 5, and Comparative Example is slightly decreased; compared with Examples 1 to 3, the high-temperature and salt resistance performance of Comparative Example 1 and Comparative Example 2 is significantly decreased. The reason for the analysis is that Comparative Example 1 does not include fluorinated copolymer, and Comparative Example 2 does not include sodium dodecylbenzenesulfonate, lacking the synergistic effect of fluorinated polymer and sodium dodecylbenzenesulfonate, resulting in a significant decrease in its temperature and salt resistance performance.

[0057] Test Example 2 Oil-Water Interfacial Tension Experiment Weigh 0.1 g of the surfactant for shale oil carbon dioxide flooding prepared in the above examples and comparative examples and dissolve it in 100 mL of brine with a salinity of 25×10 4 mg / L (20×10 4 mg / L of NaCl, 30000 mg / L of CaCl2, 20000 mg / L of MgCl2). Use a rotating drop interfacial tension meter to measure the oil-water interface with shale oil crude oil at 125 °C and measure the oil-water interfacial tension. The test results are shown in Table 2.

[0058] Table 2 Test Results of Oil-Water Interfacial Tension

[0059] As can be seen from Table 2, the surfactant for carbon dioxide flooding of shale oil provided in the embodiments of the present application can be reduced to the range of 10 - 3 mN / m. The interfacial tension between oil and water in Comparative Example 1 is the largest. The reason for the analysis is that it does not include a fluorinated copolymer, and the ability to reduce the surface tension is greatly reduced.

[0060] Experimental Example 3 Core huff and puff experiment A sand-packed tube with a length of 1000 mm and a diameter of 25.4 mm was selected for long-core displacement experiments to determine the minimum miscibility pressure and recovery rate of the system. The specific steps are as follows: (1) Add the surfactants for carbon dioxide flooding of shale oil in the embodiments and comparative examples into high-pressure closed containers respectively; (2) Then pump liquid carbon dioxide into the high-pressure closed container. The mass of the surfactant for carbon dioxide flooding of shale oil is 20% of the mass of liquid carbon dioxide. Then heat and pressurize the container to transform it into a supercritical state and control it to reach the required experimental pressure; (3) Sand filling. The core tube model was filled with quartz sand with a mesh size of 80-120. During the sand filling process, it should be done in small amounts and multiple times, and the core tube should be continuously tapped to make the sand filled tightly; (4) Vacuum pumping and weighing. The sand-packed tube was evacuated, and the dry weight of the core tube was weighed after 4 hours; (5) Water saturation: Saturate the sand-packed tube model with water, weigh the wet weight, calculate the pore volume, porosity and water permeability. If the permeability is between 1000 mD and 1500 mD, then proceed to the next step, otherwise repeat steps (1) and (2); (6) Oil saturation: Heat the oil sample used to the experimental temperature of 80 °C, and perform oil displacement of water on the water-saturated sand-packed tube. The oil saturation rate is 0.5 mL·min -1 , until no water comes out; (7) Inject CO2 for oil displacement: Connect the instrument and place it in an incubator. When the experimental temperature is reached, start the displacement experiment. Set the back pressure required for the experiment, open the valves and six-way valves of the high-pressure closed container, and the constant injection rate is 0.3 mL·min -1 , and every time 0.05 PV is injected, record the oil production, displacement pump reading. The inlet and outlet pressures of the long core are collected by a pressure acquisition box. When the cumulative gas injection exceeds 1.2 PV pore volume, stop the displacement; (8) Clean the sand-packed tube: After the displacement experiment is completed, take out the sand and clean the sand-packed tube with petroleum ether for use in the next group of experiments.

[0061] The test results are shown in Table 3.

[0062] Table 3 Test results of core huff and puff experiment

[0063] As can be seen from Table 3, Examples 1 to 3 can effectively reduce the miscibility pressure. Supercritical carbon dioxide carrying surfactant for carbon dioxide flooding of shale oil contacts with crude oil, reducing the interfacial tension in the interface between carbon dioxide and crude oil, thereby reducing its minimum miscibility pressure, making the injected carbon dioxide easily form a miscible zone with crude oil, achieving miscible flooding, and thus improving the recovery factor.

[0064] The surfactant for carbon dioxide flooding of shale oil provided by this application has good high-temperature and salt tolerance properties, can withstand a temperature of over 135 °C, and a salinity greater than 25×10 4 mg / L of brine, has high oil-water interfacial activity, and the oil-water interfacial tension with shale oil crude oil can be reduced to within the range of 10 -3 mN / m, can effectively reduce the viscosity of crude oil in core pores, the oil-gas interfacial tension, and the minimum miscibility pressure, making the crude oil flow out of the core pores more easily, and the oil displacement efficiency can reach over 69%, and it can be applied to the development of high-temperature and high-salinity shale oil reservoirs.

[0065] As mentioned above, the above are only the embodiments of this application. The protection scope of this application is not limited by these specific embodiments, but is determined by the claims of this application. For those skilled in the art, various changes and modifications can be made to this application. Any modification, equivalent replacement, improvement, etc. made within the technical idea and principle of this application shall be included within the protection scope of this application.

Claims

1. A surfactant for carbon dioxide flooding of shale oil, characterized in that, By weight parts, it includes 100 parts of water, 40 - 60 parts of fluorinated copolymer, 15 - 25 parts of sodium dodecylbenzenesulfonate, 10 - 20 parts of polyoxyethylene ether surfactant containing siloxy group, and 5 - 10 parts of nanoparticles; The nanoparticles include nano - silica and nano - alumina. The nano - silica includes modified nano - silica and unmodified nano - silica. The modified nano - silica is obtained by modification with a silane coupling agent; The preparation method of the fluorinated copolymer includes the following steps: S01 Add diethylaminoethyl methacrylate, N - isopropylacrylamide, and dodecafluoroheptyl methacrylate into a reaction vessel in sequence, add deionized water, stir evenly and heat up to 60 - 80 °C; S02 Add an initiator into the reaction vessel, stir and react for 5 - 7 h under a nitrogen atmosphere, cool and reflux to room temperature to obtain a crude product; S03 Purify the crude product by dialysis and freeze - dry it to obtain the fluorinated copolymer.

2. The surfactant for carbon dioxide flooding of shale oil according to claim 1, characterized in that, The molar ratio of diethylaminoethyl methacrylate to N - isopropylacrylamide is (3 - 5):1; the molar ratio of diethylaminoethyl methacrylate to dodecafluoroheptyl methacrylate is (1 - 3):1; the initiator is ammonium persulfate, and the mass of the initiator is 1 - 1.5% of the sum of the monomer masses.

3. The surfactant for carbon dioxide flooding of shale oil according to claim 1, wherein The mass ratio of nano - silica to nano - alumina is (2 - 5):

1.

4. The surfactant for carbon dioxide flooding of shale oil according to claim 3, wherein The modified nano - silica is prepared by modifying silica with an amino - silane coupling agent.

5. The surfactant for carbon dioxide flooding of shale oil according to claim 1, characterized in that The preparation method of the polyoxyethylene ether surfactant containing siloxy group includes the following steps: S1 Add γ - glycidoxypropyltrimethoxysilane and methoxypolyethylene glycol into a reaction vessel, add a catalyst, stir, and react at 70 - 90 °C for 3 - 5 h under a nitrogen atmosphere; S2 Add methanol into the reaction system, and react at 70 - 90 °C for 2 - 3 h under a nitrogen atmosphere to obtain a crude product; S3 Obtain the polyoxyethylene ether surfactant containing siloxy group through vacuum distillation, dialysis, and concentration.

6. The surfactant for carbon dioxide flooding of shale oil according to claim 5, wherein, The molar ratio of γ - glycidoxypropyltrimethoxysilane to methoxypolyethylene glycol is 1:(1 - 1.3); the mass of the catalyst is 0.5 - 1% of the total mass of γ - glycidoxypropyltrimethoxysilane and methoxypolyethylene glycol; the molar ratio of methanol to methoxypolyethylene glycol is (1 - 2):

1.

7. The surfactant for carbon dioxide flooding of shale oil according to claim 5, wherein The catalyst includes tetrabutylammonium hydroxide.

8. The preparation method of the surfactant for carbon dioxide flooding of shale oil according to any one of claims 1 to 7, characterized in that, It includes the following steps: (1) Add the fluorinated copolymer into water and stir evenly; (2) Add sodium dodecylbenzenesulfonate and the polyoxyethylene ether surfactant containing siloxy group in sequence and stir evenly; (3) Ultrasonically disperse the nanoparticles in water to form a dispersion, add it to the mixed solution in step (2), stir and then circulate and homogenize 2 - 3 times through a high - pressure homogenizer; (4) Adjust the pH value, cool to room temperature and filter to obtain the surfactant for shale oil carbon dioxide flooding.

9. The preparation method of the surfactant for carbon dioxide flooding of shale oil according to claim 8, characterized in that, In step (1), the temperature of water is 40 - 50 °C.

10. The preparation method of the surfactant for carbon dioxide flooding of shale oil according to claim 8, characterized in that, In step (3), the pressure of cyclic homogenization is 1000 - 2000 PSI; in step (4), the pH value is 6 - 8.

Citation Information

Patent Citations

  • Method for improving carbon dioxide displacement yield by using surfactants

    CN105257264A

  • Fluorine-containing acrylic ester polymer-modified nano silicon dioxide scrubbing oil system, and preparation method and application thereof

    CN104341799A

  • Fluidity control system for CO2 flooding of low permeability or ultra-low permeability reservoir and use thereof

    CN107365576A

  • Thickened carbon dioxide oil displacement efficient thickening agent and preparation method thereof

    CN115703862A

  • Modified nano oil displacement agent and preparation method thereof

    CN118064118A

Cited By

  • Fracturing oil-displacing agent and preparation process thereof

    CN120829770A

  • Intelligent nanocapsule oil-displacing agent as well as preparation method and application thereof

    CN121975509A

  • Intelligent nano-capsule oil-displacing agent, preparation method and application thereof

    CN121975509B